2006
DOI: 10.1016/j.pcl.2006.08.004
|View full text |Cite
|
Sign up to set email alerts
|

The Cell Biology of Acute Childhood Respiratory Disease: Therapeutic Implications

Abstract: Respiratory syncytial virus (RSV), the recently identified human metapneumovirus (HMPV), and the human parainfluenza viruses (HPIVs), cause most cases of childhood croup, bronchiolitis, and pneumonia. Influenza virus also causes a significant burden of disease in young children, although its significance in children was not fully recognized until recently. This article discusses pathogens that have been studied for several decades, including RSV and HPIVs, and also explores the newly identified viral pathogens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 176 publications
(207 reference statements)
0
21
0
Order By: Relevance
“…Among our findings, we have shown that a minimal, physiologically relevant inoculum of PVM (typically <100 pfu) results in robust virus replication in lung tissue, accompanied by influx of granulocytes in response to local production of specific proinflammatory chemokines [8]. The pathophysiology of PVM bronchiolitis leading to pneumonia and acute respiratory distress syndrome (ARDS) is similar to that observed in response to severe respiratory syncytial virus (hRSV) infection in human infants [9]. …”
Section: Resultsmentioning
confidence: 91%
“…Among our findings, we have shown that a minimal, physiologically relevant inoculum of PVM (typically <100 pfu) results in robust virus replication in lung tissue, accompanied by influx of granulocytes in response to local production of specific proinflammatory chemokines [8]. The pathophysiology of PVM bronchiolitis leading to pneumonia and acute respiratory distress syndrome (ARDS) is similar to that observed in response to severe respiratory syncytial virus (hRSV) infection in human infants [9]. …”
Section: Resultsmentioning
confidence: 91%
“…There are no effective vaccines or treatments for the HPIVs. Remarkably, while strategies of passive immunoprophylaxis for RSV protect infants at greatest risk (9), and effective antiviral drugs and vaccines are available for influenza (10,11), there are no vaccines or drugs for the HPIVs (1,12).…”
mentioning
confidence: 99%
“…The parainfl uenza viruses types 1 and 3 belong to the Respirovirus genus within the Paramyxovirinae subfamily of the Paramyxoviridae family of negative-stranded RNA viruses, while parainfl uenza virus type 2 belongs to the Rubulavirus genus. Human parainfl uenza viruses (HPIVs) cause lower respiratory tract diseases including bronchitis, bronchiolitis, and pneumonia in infants, children, and immunocompromised individuals [ 3 ] and are responsible for up to 30-40 % of all acute respiratory tract infections in infants and children. In adults, the impact of these respiratory viruses may be serious as well.…”
Section: Introductionmentioning
confidence: 99%